2021
DOI: 10.32007/jfacmedbagdad.6331846
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D level and telogen hair loss: A Case control study

Abstract: Abstract   Background: Hair loss is a common skin condition. Hair is not a vital organ but losing it has a worse effect on the psychological state of the patient and may interrupt his daily social activities. Telogen effluvium founded to be the commonest noninflammatory cause to diffuse hair loss. Since nutritional disturbances are one of the triggering factors for it. It might be useful in the management of TE Due to the limited number of studies& little information is available on this subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Animals treated with Group V showed statistically non-significant reduction in ( WBC) and (elevation in platelets) levels (P>0.05) compared to level in rats with levofloxacin(50mg/kg/day) alone Group II while animals showed non-significant elevation in platelets and reduction WBC (P>0.05) of rats with Group VI compared to Group III and group V had higher platelets and lowest WBC in contrast group VI these results consistent with previous studies (39) (40) .Additionally ، levofloxacin ، which decreased the rats platelet counts during treatment ، may cause mild blood coagulation abnormalities (41) . The thrombocytopenia seen in this study could be caused by either enhanced drugmediated destruction or decreased platelet synthesis as seen in bone marrow suppression (42) ، Given that the rats utilized in this investigation were healthy and had normal blood parameters ، this study concluded that extended treatment of levofloxacin may result in anemia as well as thrombocytopenia (43) (44) .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Animals treated with Group V showed statistically non-significant reduction in ( WBC) and (elevation in platelets) levels (P>0.05) compared to level in rats with levofloxacin(50mg/kg/day) alone Group II while animals showed non-significant elevation in platelets and reduction WBC (P>0.05) of rats with Group VI compared to Group III and group V had higher platelets and lowest WBC in contrast group VI these results consistent with previous studies (39) (40) .Additionally ، levofloxacin ، which decreased the rats platelet counts during treatment ، may cause mild blood coagulation abnormalities (41) . The thrombocytopenia seen in this study could be caused by either enhanced drugmediated destruction or decreased platelet synthesis as seen in bone marrow suppression (42) ، Given that the rats utilized in this investigation were healthy and had normal blood parameters ، this study concluded that extended treatment of levofloxacin may result in anemia as well as thrombocytopenia (43) (44) .…”
Section: Discussionsupporting
confidence: 85%
“…In addition ، vitamin D has improved erythropoiesis ، inhibited premature erythrocyte lysis ، prevented polyunsaturated fatty acid oxidation in the erythrocyte membrane ، and increased the amount of erythroid precursor units forming colonies (46) (47) . Levofloxacin has been linked to changes in a variety of blood parameters in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be generalized as getting after a severe illness, nutritional deficiency, drug, emotional stress, infection, or other physiologic trauma. The localized TE seen in inflammatory diseases such as psoriasis and seborrheic dermatitis [4,[19][20][21], as well as post-hair transplantation [22]. Several articles suggested religious headwear and hijab were associated with secondary TE through aggravating underlining seborrheic dermatitis of the scalp [23,24].…”
Section: Mechanisms Of Hair Shedding and Thementioning
confidence: 99%
“…Variations in hair texture can serve as valuable indicators of underlying vitamin deficiencies [ 9 , 10 ]. Consequently, people often inquire about vitamin supplementation as a potential means to prevent or treat dermatological conditions, particularly hair loss [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%